Allogeneic hematopoietic stem cell transplantation could improve survival of cytogenetically normal adult acute myeloid leukemia patients with DNMT3A mutations. Issue 11 (November 2015) - Xu, Yang; Sun, Yanjun; Shen, Hongjie; Ding, Lin; Yang, Zhen; Qiu, Huiying; Sun, Aining; Chen, Suning; Wu, Depei
<x xml:space="preserve">Abstract</x> DNMT3A mutations are frequent in cytogenetically normal acute myeloid leukemia (cn‐AML) patients and associated with poor survival. The role of allogeneic hematopoietic stem cell transplantation (allo‐HSCT) in DNMT3Amut cn‐AML patients remains unclear. In this study, we retrospectively analyzed the prognostic impact of DNMT3A mutations and explored the role of allo‐HSCT in 308 cn‐AML patients who received consolidation of intensive chemotherapy or allo‐HSCT in our center from March 2005 to May 2014. In the whole cohort, 63 patients (20.5%) were identified with DNMT3A exon 23 mutations and R882H was the most frequent variant. DNMT3Amut patients had shorter overall survival (3‐year OS: 31.9% vs. 52.0%, P = 0.009) and disease‐free survival (3‐year DFS: 21.8% vs. 40.1%, P = 0.004) compared with DNMT3Awt patients. Based on FLT3/NPM1/CEBPA mutations, 308 cn‐AML patients were divided into favorable/intermediate group (n = 262) and unfavorable group (n = 46). There were no significant differences in 3‐year OS and 3‐year DFS between DNMT3Amut and DNMT3Awt patients in both favorable/intermediate and unfavorable groups. Additionally, in multivariate analysis, DNMT3A mutation remained an independent adverse prognostic factor for the survival. In the DNMT3Amut cohort, 23 complete remission (CR) patients received allo‐HSCT consolidation and 32 CR patients received chemotherapy consolidation, dramatic differences were observed in 3‐year OS (51.7% vs. 28.9%, P = 0.048) and 3‐year DFS (41.6% vs. 14.9%, P = 0.024) between allo‐HSCT group and chemotherapy group. Collectively, DNMT3A mutation is a poor prognostic factor for cn‐AML patients and allo‐HSCT could improve survival of cn‐AML patients with DNMT3A mutations. Am. J. Hematol. 90:992–997, 2015. © 2015 Wiley Periodicals, Inc.